Területi érdek és a vasúti közlekedés - Erdősi, Ferenc (Tér és Társadalom, 1987)
Researchers in Hungary have yet paid much attention to the factors and socio-economic conditions that contribute to the formation of the so-called „linear" infrastructure, including communications networks. They have mostly concentrated on the reasons and factors that influence the location of industrial plants that can be represented in a „one-point" economic model. In his stop-gap research the author considers regional interest to be the most decisive socio-economic factor in shaping, developing and modifying the spatial structure of modern transport, and within this the railway network. (Regional interest, in its most general interpretations means the basically economic interest of people of different sexes, ages, qualification and social status, related to their residence or the environment in which they spend their leisure. The population is directly interested in properly maintaining, shaping and supplying with infrastructure these locations that constitute their common environment.) The present research has revealed that it is the confrontation of interests between regional units of different hierarchic ranking and quite frequently the various sectors (e.g. mining, agrarian-industriall or in some cases the resulting compromises that created the present network which can only partly come up to the requirements of today’s spatial system of production and settlement network. The Austrian Monarchy that, in an autocratic way, annexed Hungary, was interested in establishing a network with its main railway line between Vienna and Triest, avoiding the largest Hungarian economic-social centre, Budapest, to ensure cheap wheat imports for Austria and increase profits of Austrian Commercial Houses. These interests, however, could only be partly realized by the construction of a few railway lines because of the opposition of the Hungarian national interests that called for a monocentrical network to make Budapest a pendant of Vienna while wheat exports would have been realized at external markets through Fiume. After the compromise of 1867, and from tha 1880s in particular, the centralist Hungarian state policy, supported by the lobby of food industrialists in Budapest, managed to create a capitalcentred network, stopping the construction of the transversal lines that had already started. This extremely monocentrical concept changed only after the turning of the century. Branch lines were built by local railway companies; their routes and the settlements they were to connect largely depended upon the regional interests of trading and industrial chámbers, the provincial interests enforced with various autocratic and financial means by the county organs, as well as the local interests represented by the settlement administration. The study contains a lot of examples to illustrate these statements and also analyzes the economic aspects of these regional interests.